Template-free fabrication of vertically-aligned polymer nanowire array on the flat-end tip for quantifying the single living cancer cells and nanosurface interaction. (April 2018) - Wang, Biran; Wang, Liming; Li, Xi; Liu, Yuchen; Zhang, Zimeng; Hedrick, Erik; Safe, Stephen; Qiu, Jingjing; Lu, Guohui; Wang, Shiren
Abstract: We fabricated vertically aligned polyaniline (PANI) nanowire arrays on flat-end AFM tips via template-free methods. 4-Aminothiophenol was used for tailoring the nucleation size, chain propagation and orientation of the PANI nanowires. The microscopy characterization indicated that diameter was centered at a mean of 33.7 nm with a standard deviation of 6.5 nm, and length was centered at a mean of 50.3 nm with a standard deviation of 7.6 nm. PANI nanowire arrays are non-toxic, low-cost, and tunable, and thus PANI nanowire-grown tips could perfectly simulate different nanosurfaces. Via the force spectroscopy, we demonstrate the feasibility in real-time quantifying the nanostructure-cell interactions at the single cell level with high reliability and accuracy. This work will enable a new tool in precisely quantifying the interactions of single living cells and nanosurface, and thus opens a new door to understand how single living cells sense and respond to the specific nanostructures.